UMP explores international collaboration with Turkey’s BAIBU - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) continues to enhance its strategic international relations by exploring academic and research opportunities with Bolu Aybant Izzet University (BAIBU) of Turkey at the recent Asia-Pacific Association for International Education (APAIE) Convention 2019, held at the Kuala Lumpur Convention Centre on March 27, 2019.